In Vitro Models for Anti-Aging Efficacy Assessment: A Critical Update in Dermocosmetic Research - Ana M. Cruz; Margarida C. Gonçalves; Matilde S. Marques; Francisco Veiga; Ana Cláudia Paiva-Santos; Patrícia C. Pires (Cosmetics, 2023)
The skin is the human body’s largest organ and serves as a crucial boundary between the body and the external environment. As a natural process, skin aging cannot be avoided, and it causes changes in the skin’s strength, structure, elasticity, and integrity. Many approaches have been developed over the years to study the skin, including in vivo and in vitro methods. Nevertheless, animal assays have ethical issues and a lack of reproducibility. Hence, in vitro skin models have been increasingly developed and used. For the assessment of the potential of the anti-aging activity of compounds of different origins, the most commonly used in vitro assays are the ones evaluating antioxidant, anti-collagenase, anti-elastase, anti-hyaluronidase, anti-tyrosinase, anti-inflammatory, antiglycation, or moisturizing activity, and the induction of skin cell proliferation/anti-senescence effects or the inhibition of matrix metalloproteinase production. The purpose of this review is to summarize the most commonly used in vitro models for the evaluation of skin aging and cometic products’ anti-aging efficacy, providing a useful guide for researchers in the field. Overall, these assays provide important data on the safety and efficacy of anti-aging compounds, and a foundation for research on and the eventual introduction of formulations into the cosmetics market.